2019
DOI: 10.1371/journal.pone.0211249
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional changes in weight status and weight related behaviors among Australian children and Australian Indigenous children between 2010 and 2015

Abstract: Background Since 2006 there has been substantial long-term investment in school-based child obesity prevention programs in New South Wales (Australia). Whether these programs have led to population level improvements in children’s weight status and weight-related behaviors are yet to be determined. The purpose of this study was to describe changes in children’s weight status and weight-related behaviors, including Indigenous children, who are at greater risk of poorer health outcomes than non-Indi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The data collected throughout the SPANS series made a substantial contribution to the evidence-base for different policy areas and the development of programs. The trends in in overweight and obesity highlight that children from low socioeconomic status (SES) areas (especially adolescents) [ 12 ], cultural and linguistically diverse language backgrounds [ 13 ], and of Aboriginal and Torres Strait Island heritage [ 14 ] would benefit from targeted interventions or programs. In 2010, it was found that one in five children entering the first year of school had overweight and obesity [ 15 ], highlighting that weight-related behaviours are established in the child’s home environment.…”
Section: Introductionmentioning
confidence: 99%
“…The data collected throughout the SPANS series made a substantial contribution to the evidence-base for different policy areas and the development of programs. The trends in in overweight and obesity highlight that children from low socioeconomic status (SES) areas (especially adolescents) [ 12 ], cultural and linguistically diverse language backgrounds [ 13 ], and of Aboriginal and Torres Strait Island heritage [ 14 ] would benefit from targeted interventions or programs. In 2010, it was found that one in five children entering the first year of school had overweight and obesity [ 15 ], highlighting that weight-related behaviours are established in the child’s home environment.…”
Section: Introductionmentioning
confidence: 99%
“…The Queensland Heath report found that in 2011-2012 teenagers (aged 14-18 years) derived 45% of daily total energy from unhealthy foods and 32% consumed snack food daily (Queensland Health 2018). Similarly Hardy et al (2019) found that in 2015, 25% of children had a high junk food intake;…”
Section: Healthiness and The Prevalence Of Discretionary Foodsmentioning
confidence: 93%
“…Australia's Health 2016 report found that 97% of children did not eat the recommended daily servings of vegetables and 30% did not eat the recommended daily servings of fruit (Australian Institute of Health and Welfare 2016). Furthermore, 26% of children (aged 5-14) and 37% of young people (aged 15-24) were overweight or obese (Australian Institute of Health and Welfare 2016), with these trends continuing to increase particularly for Indigenous children (Hardy et al 2019). Most alarmingly, discretionary foods (often energy rich food and drinks high in saturated fats, sugars and/or salt) contributed 39% of energy intake for children and young people during 2011-2012 (Australian Institute of Health and Welfare 2016).…”
Section: Food Systems Urban Agriculture and Food Securitymentioning
confidence: 99%
See 2 more Smart Citations